PENGARUH VARIETAS DAN TIPE STARTER TERHADAP KADAR AIR, KADAR PROTEIN KASAR, DAN KADAR SERAT KASAR PADA SILASE TEBON JAGUNG - Susan Dian Mirsani; Rudy Sutrisna; Agung Kusuma Wijaya; Liman Liman (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
This study aimed to investigate the effect of different varieties and type of starter on moisture, crude protein, and crude fibre of corn forage silage. This research was conducted in May - August 2019 at the Laboratory of Nutrition and Animal Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design used was a factorial Complete Randomized Design (CRD) with 3 replications. The factors studied were (1) corn forage varieties, which consisted of two varieties, namely BISI-18 and NK-212 and (2) type of starter, which consisted of two types, namely molasses and bran. The results showed that there was no interaction (P> 0.05) between variety of corn forages and type of starter on moisture content, crude protein, and crude fiber content. The use of different corn forage varieties had no significant effect (P> 0.05) on moisture content, crude protein, and crude fiber content. The use of different types of starter had no significant effect (P> 0.05) on moisture content, crude protein, and crude fiber content. Keywords: Crude fibre, Crude protein, Moisture content, Starter, Varieties